THE APPLICATION OF BALANCED SCORECARD APPROACH AS THE YARDSTICK OF BANK PERFORMANCE ASSESSMENT - Setiadi, Pompong Budi; Ursula S., Ratna; Rahayu, Sri (International Journal For Research In Business, Management And Accounting, 2021)
The objective of research is to understand and to examine how good is the performance of BPR Dinar Pusaka at Sidoarjo based on the use of balanced scorecard approach, especially concerning with the measurement of performance with financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. Method used in this research is quantitative data analysis. Result of calculation and analysis is then used as the base for decision-making or also as the reference in making conclusion whether the performance of bank management is good or not if measured using balanced scorecard approach. This position is supported by Dahlan and Siamat, Tawaf and Tjukria, P, Kaplan and Norton, Yuwono, Sukarno, and Ichsan, Ratnawati, Mulia, Sutrisno Hadi, Husien Umar, Mulyadi, and Suharsimi Arikunto. Pursuant to the result of research, the conclusion is made as following: (1) Financial perspective at BPR Dinar Pusaka is described by the increase of the ratios of asset quality and efficiency and the decline of the ratios of capitalization, rentability and liquidity. (2) Customer perspective at BPR Dinar Pusaka is explained by the increase of customer retention and customer profitability rates and the satisfaction of saving customers and credit customers, but with the decline of customer acquisition. (3) Internal business process perspective at BPR Dinar Pusaka is indicated by the increase of receivable circulation rate, the improved timings for credit service process and saving service process, and the reduced level of uncollected receivable risk. (4) Learning and growth perspective at BPR Dinar Pusaka is reflected by the increase of employee training rate and employee satisfaction rate but with the decline of employee productivity rate.